The Gamifying Cooperative Learning: The Impact of Team Games Tournament and Wordwall Media on Student Engagement in Elementary Science Education - Dela Aprilia Damayanti; Pinasti Dwi Utami; Alfian Bayu Sutanto; Naufal Ishartono; Diana Novita Lestari (Jurnal VARIDIKA, 2025)
This study addresses the critical pedagogical challenge of low student engagement in learning the Natural and Social Sciences (NSS) topic, particularly manifested through passive participation and limited focus during collaborative activities. Employing a classroom action research framework across two iterative cycles – each comprising planning, implementation, observation, and reflective evaluation phases – the investigation examines the efficacy of combining the Team Games Tournament (TGT) cooperative learning model with interactive Wordwall media in revitalizing student participation. The research cohort consisted of 25 fourth-grade students at SD Negeri Pucangan 03, with data triangulated through systematic observation, semi-structured interviews, and documentary analysis. Initial baseline assessments revealed only 50% student engagement levels, highlighting the urgency for pedagogical intervention. Implementation of the TGT-Wordwall integration yielded substantial improvements, with engagement metrics rising to 74% in Cycle 1 and further escalating to 84% in Cycle 2, demonstrating consistent positive trajectory. The findings substantiate that gamified cooperative learning strategies effectively transform passive learners into active participants by leveraging competitive team dynamics coupled with digital interactivity. This pedagogical synergy not only enhanced immediate lesson engagement but also fostered sustained interest in the NSS curriculum. The study contributes to contemporary educational discourse by providing empirical evidence for technology-enhanced cooperative learning models in elementary STEM education, while offering a replicable framework for addressing engagement deficits in comparable contexts. Practical implications suggest the potential for broader application of integrated TGT-digital approaches across subject domains requiring high conceptual engagement and collaborative problem-solving competencies.